Determinan Pencegahan Penyakit DBD di Wilayah Kerja Puskesmas Melati Kuala Kapuas - Irianty, Hilda; Febriyanti, Ervina; Rizal, Achmad; Norfai, Norfai (Universitas Baiturrahim, 2026)
Prevention of dengue disease is an effort made to prevent the transmission and spread of the dengue virus carried by the Aedes aegpty mosquito. Based on data obtained from the Melati Health Center in Kuala Kapuas City, dengue cases in the Melati Health Center's work area reached 47 cases in 2022 and increased to 50 cases in 2023. The purpose of this study is to identify and analyze the relationship between education, knowledge, and attitudes towards dengue disease prevention in the working area of the Melati Health Center in 2025. This type of research is a quantitative research with a cross-sectional approach. The population in this study is housewives who live in the Central Straits sub-district of the working area of the Melati Health Center, Kuala Kapuas City. The sample in this study amounted to 97 respondents with Accidental Sampling technique. Data collection with a questionnaire consisting of 10 statements of dengue prevention, 10 knowledge questions and 10 attitude statements were analyzed univariate and bivariate and analyzed using the chi square test. The results of the analysis of Univariate of this study showed that of the 97 respondents, most of them had poor dengue disease prevention, namely 51 respondents (52.6%), low education as many as 53 respondents (54.6%), good knowledge as many as 42 respondents (43.3%), and positive attitudes as many as 73 respondents (75.3%). The results of the bivariate analysis tested in the chi square showed that there was a relationship between Education (p-value = 0.000 < α = 0.05), Knowledge (p-value = 0.000 < α = 0.05) and Attitude (p-value = 0.000 < α = 0.05) towards the prevention of dengue disease. From the educational results, the respondents have a low category with low education greatly affects the respondents' knowledge about dengue prevention, but from the knowledge there are still many who are knowledgeable because the respondents have monitored mosquito larvae in water reservoirs and also think positively in taking preventive measures. Suggestions are expected to the community to routinely carry out 4M Plus in preventing the transmission and spread of dengue disease in the surrounding environment